Uma abordagem baseada em texels para síntese de texturas que variam progressivamente - Tonietto, Leandro (Universidade do Vale do Rio do Sinos, 2005)
We present a model for texture synthesis from samples, particularly for synthesis of textures with smooth variation of the texture elements, known as Progressively-Variant Textures (PVT). This type of textures is common in Nature, specially in animal coat markings such as leopards. Current solutions, for the most part, do not allow much control by the user or the ones which do allow control are limited or have problems due to the pixel-at-a-time nature of synthesis. We address these problems with the introduction of an algorithm based on a new building block for synthesis: the texel. Our solution builds a new texture grouping texels which satisfy a neighborhood similarity criterion. The PVT features are introduced with affine transformations and morphological operators defined by the user and applied to the texels. The results show a good visual quality for a large number of sample textures, including cases where current solutions for natural textures fail. Besides, the many possibilities for variation of te
Keywords: computação grafica; preenchimento de textels; síntese de texturas; variação progressiva; Progressively-Variant Textures; texture synthesis; Ciências Exatas e da Terra